Krafty kids : a communications campaign aimed at encouraging parents to nurture creativity by actively facilitating arts and crafts with their children ages 4 to 7 - Hsu, Bridget Li-Wen (Nanyang Technological University, 2020)
This paper presents Krafty Kids, a non-profit public communications campaign by four final-year students from Wee Kim Wee School of Communication and Information, Nanyang Technological University (WKWSCI, NTU). Krafty Kids was conceptualised to educate and empower parents to nurture their child's creative development. This paper will highlight the importance of nurturing creativity, particularly among children from the ages 4 to 7. Creativity is increasingly being touted as an important asset in the 21st century. It encourages out-of-the-box thinking and innovation, which are key attributes for success and growth. Children in that age are the most innately curious and creative, and these traits tend to decline as they grow older and enter education institutions. Parents in Singapore place high stakes on their children’s education and learning. By having parents play an active role in a child’s learning, it creates a supportive environment for the children to grow and gain more confidence in their creativity and thinking. Arts and crafts is known to combine various elements of learning as it involves both creative and cognitive development, with the added benefits of nurturing their physical and motor skills. This paper uses both quantitative and qualitative research to understand the impacts of our strategies on young children. Our findings demonstrate that empowering parents with the knowledge and confidence to facilitate arts and crafts were effective in increasing behaviour and intention.